Read and write with all your senses: a multisensory method for learning to read and write in neurodevelopmental disorders - Santos, Catarina (2018)
Reading and writing learning difficulties are commonplace in today's schools. Therefore, researching teaching methodologies that allow children to achieve academic success is a matter of extreme urgency. Through the development and implementation of a multisensory methodology based teaching program, this research project aims at documenting and understanding any changes in reading and writing learning processes. Using a qualitative multiple case study methodology, five participants were selected by convenience according to the following three criteria: Intellectual and Developmental Disabilities, Phonological Disorders and severe learning difficulties. Through the use of tools such as Infant/Toddler Sensory Profile and Language Competencies Evaluation for Reading and Writing there was, correspondingly, the possibility of mapping the sensory profile of each participant and verifying his/her learning development during the program, in the areas of phonological awareness, reading and writing. The multisensory program was applied during weekly interventions over a period of four months. Results showed improvement in the participants’ reading and writing learning process. It is also worth mentioning that, despite not being a goal of this research, there was also an increase of the phonological awareness of all participants. The multisensory methodology integrates strategies in its structure that include a greater number of sensory aids, like visual and audition aids, as well as kinesthetic and tactile aids. The increase of this type of aids proved to work as a compensation technique which allowed the child to achieve a greater probability of success in his reading and writing learning process.